Implementation Of Standard Operational Procedure (Sop) In Improving Service Efficiency In The Banking Industry - Rukmana, Febi Indriyanti (Politeknik Siber Cerdika Internasional, 2023)
In an organization, industry, or situational activity, there are always rules or procedures that are correct for doing every job in an organization, industry, or event. This is known as an SOP (STANDARD Operational Procedure), according to the meaning SOP is used to manage employees or remind employees of good and correct operational procedures. SOPs are often heard in technology industries such as machinery, electricity, mining, and other technical issues. However, in fact SOPs are implemented in all areas of industry including banking. The banking industry certainly has SOPs for its employees, SOPs are carried out so that employees carry out work as they should, starting from behaving towards customers to financial calculations. The application of SOPs is also expected to be able to help improve service efficiency because SOPs are the best performance guidelines that are expected to be carried out by every employee. Efficiency is related to time, the indicator of achieving the word efficient is whether or not time is used. This study focuses on the influence of SOPs in increasing service efficiency in the banking industry. This study uses a qualitative method of literature study approach. This research resulted in an understanding that the application of SOPs can improve service efficiency in the banking industry because by adhering to SOPs, of course work can be completed in the best way and results.